2018
DOI: 10.21037/atm.2017.10.22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of dispensing granules with traditional decoction: a systematic review and meta-analysis

Abstract: as effective as the traditional decoction kept unclear. This systematic review and meta-analysis was made to assess the efficacy of dispensing granules compared with traditional decoction. Methods:We searched four databases since their inception to 9th September in 2016. Two authors independently identified trials, extracted data and assessed risk of bias with Cochrane Reviewer's Handbook 5.0. We conducted meta-analysis with RevMan 5.1.0 software for eligible and appropriate trials.Results: In the end, 7,035 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 7 publications
(11 reference statements)
0
11
0
1
Order By: Relevance
“…The equivalence between dispensing granules and standard decoction remains unknown. Recent meta-analysis, which reviewed the efficacy of dispensing granules and traditional decoctions, revealed that the clinical evidence for dispensing granules is controversial (Qiu, Zhang, Zhao, Li, & Shang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The equivalence between dispensing granules and standard decoction remains unknown. Recent meta-analysis, which reviewed the efficacy of dispensing granules and traditional decoctions, revealed that the clinical evidence for dispensing granules is controversial (Qiu, Zhang, Zhao, Li, & Shang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Integrated clinics are increasingly common globally and provide a platform for physicians from different streams to design and evaluate IM protocols [48]. High quality decoctingfree herbal granules provide patients more standardised and user-friendly administration for long-term use [49].…”
Section: Implications For Practice Organisation and Policymentioning
confidence: 99%
“…With the increasing development of TCM granules, international research has focused on whether decoction can be replaced by granules with similar effectiveness and safety [15]. During the procedure of granule preparation, the difference of water extraction, concentration, desiccation and granulation may influence the dissolution and chemical profiles of active ingredients [85]. Thus, this may result in different clinical efficacy between granules and decoction.…”
Section: Modern Granular Formulationsmentioning
confidence: 99%